2007
DOI: 10.3102/0002831206298171
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Science Knowledge, Reading Skill, and Reading Strategy Knowledge on More Traditional “High-Stakes” Measures of High School Students’ Science Achievement

Abstract: This study examined how well cognitive abilities predict high school students’ science achievement as measured by traditional content-based tests. Students (n = 1,651) from four high schools in three states were assessed on their science knowledge, reading skill, and reading strategy knowledge. The dependent variable, content-based science achievement, was measured in terms of students’ comprehension of a science passage, science course grade, and state science test scores. The cognitive variables reliably pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
130
3
9

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 191 publications
(156 citation statements)
references
References 92 publications
(151 reference statements)
14
130
3
9
Order By: Relevance
“…There are many different points of view, a fact which makes it a contested area (Kahle 2004;Penner 2008;Guo, Tsang, Ding 2010). Some of these studies have shown significant gender achievement gaps, with boys generally outperforming girls in Math and Science (O'Reilly, McNamara 2007;Penner 2008;Else-Quest, Hyde, Linn 2010) and girls excelling at literacy subjects. Others noted that these differences were not consistent.…”
Section: Gender and Academic Achievementmentioning
confidence: 99%
See 1 more Smart Citation
“…There are many different points of view, a fact which makes it a contested area (Kahle 2004;Penner 2008;Guo, Tsang, Ding 2010). Some of these studies have shown significant gender achievement gaps, with boys generally outperforming girls in Math and Science (O'Reilly, McNamara 2007;Penner 2008;Else-Quest, Hyde, Linn 2010) and girls excelling at literacy subjects. Others noted that these differences were not consistent.…”
Section: Gender and Academic Achievementmentioning
confidence: 99%
“…Many reasons are behind the desire to achieve academic performance. Some students, for example, seek self-satisfaction or want to demonstrate their competences while others try to attain high academic achievement to satisfy their parents or teachers by showing them that they are making efforts and working hard (O'Reilly, McNamara 2007). In the same way, parents desire and encourage their children to aspire to outstanding academic achievement while teachers adopt different strategies to ensure effective teaching and learning so that their students get good grades and perform well.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas low-knowledge readers are unable to make such inferences, high-knowledge readers (who have more background knowledge but do not know the information in the text) are more likely to be successful. Thus, higher knowledge readers can benefit from cohesion gaps because lower cohesion forces readers to generate inferences to fill in the conceptual gaps in the texts and high-knowledge readers have sufficient knowledge to generate meaningful inferences (McNamara, 2001;O'Reilly & McNamara, 2007). Successfully generating inferences aids memory and learning because prior knowledge and the information in the text are more likely to be connected in the readers' mental representation of the text, and the reader's mental representation is likely to be more coherent as a result.…”
Section: Written Communication 27(1)mentioning
confidence: 99%
“…Desde un punto de vista teórico, nuestros resultados enriquecen la investigación sobre la comprensión de textos (e. g., O'Reilly y McNamara, 2007;Ozuru et al, 2009) aportando evidencia sobre dos puntos clave. Primero, no sólo son el conocimiento previo de los estudiantes relacionado con el tema y las preguntas que generan los que parecen contribuir a su comprensión lectora de textos de ciencias, sino también variables adicionales tales como el modo en que enfocan su aprendizaje en ciencias.…”
Section: Discussionunclassified